Indirect constraints on the triple gauge boson couplings from Z → bb partial width: An update - Eboli, O. J P [UNESP]; Gonzalez-Garcia, M. C. [UNESP]; Novaes, Sérgio Ferraz [UNESP] (My University, 2000)
We update the indirect bounds on anomalous triple gauge couplings coming from the non-universal one-loop contributions to the Z → bb width. These bounds, which are independent of the Higgs boson mass, are in agreement with the standard model predictions for the gauge boson self-couplings since the present value of R(b) agrees fairly well with the theoretical estimates. Moreover, these indirect constraints on Δg(Z)/1 and g(Z)/5 are most stringent than the present direct bounds on these quantities, while the indirect limit on λ(Z) is weaker than the available experimental data.
Keywords: analytic method; chirality; coupling factor; data analysis; molecular recognition; phenomenology; standard